EFFECT OF SOLVENT COMPOSITIONS ON OIL INDICATORS IN COTTON OIL EXTRACTION - Yulchiev, Aslbek; Nasriddinov , Dilshod; Serkaev, Qamar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article studies the effect of solvent compositions obtained by mixing extraction gasoline with other organic solvents, especially ethanol and acetone, used in traditional technology for processing cottonseeds by extraction, on the physicochemical parameters of the oil. The results of the study showed that when performing the direct extraction process of cottonseeds, the solvent composition obtained in the ratios of 60:40 and 70:30, together with extraction gasoline, gave significantly better results than those obtained in other ratios. The conducted studies showed that the use of solvent raw materials instead of one type of solvent in the extraction of cottonseed oil was found to be effective. It was proven that increasing the proportion of extraction gasoline in the solvent composition changes directly proportionally to the micelle concentration and inversely proportionally to the acid value of the oil.